Cinnamtannin B-1 Prevents Ovariectomy-Induced Osteoporosis via Attenuating Osteoclastogenesis and ROS Generation - Li, Meng; Hao, Li; Li, Lei; Liu, Lei; Chen, Guang; Jiang, Wei; Xu, Wei; Zhu, Chen; Yao, Gang; Fang, Shiyuan (Frontiers in Pharmacology, 2020)
Osteoporosis (OP) is one of the common bone metabolic diseases that endangers postmenopausal women and the elders. Both excessive bone resorption caused by osteoclast over-activation and increased oxidative stress are associated with osteoporosis. Cinnamtannin B-1 (CB-1) is considered as a high-valued plant extract monomer due to its antioxidant properties. However, the mechanism of CB-1 impacts on reducing oxidative stress, inhibiting the production of reactive oxygen species (ROS) and osteoclast differentiation and preventing ovariectomy-induced osteoporosis are still unclear. In this study, the effects of CB-1 on nuclear factor κB (RANKL)-induced osteoclasts formation and differentiation in vitro and the potential therapeutic effect on ovariectomy (OVX)-induced osteoporosis in vivo are investigated. CB-1 was found to inhibit osteoclast formation and bone resorption function in a dose-dependent manner, and it inhibited specific genes related to osteoclast as well. Micro-CT and histopathological staining showed that CB-1 can effectively prevent OVX-induced osteoporosis. In addition, CB-1 treatment can effectively inhibit the production of reactive oxygen species (ROS) in vivo and in vitro. Mechanistically, CB-1 inhibits the activation of osteoclasts by inhibiting the activation of the NF-κB signaling pathway. In conclusion, CB-1 would be able to be used as a promising new drug strategy to inhibit RANKL-induced osteoclastogenesis and prevent ovariectomy-induced osteoporosis.